Pertunjukan Tong-Tong Sèrèk sebagai Cerminan Budaya Madura: Telaah Kritis Tradisi Perspektif Richard Hoggart - Albaburrahim Albaburrahim; Moh. Hafid Effendy; Moh. Badruddin Amin; Imam Suyitno; Wahyudi Siswanto (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Tong-Tong Sèrèk is one of the traditional performances of the Madurese people, rich in social values, community solidarity, and expressions of folk culture. This article aims to examine the Tong-Tong Sèrèk performance as a reflection of culture and a symbol of resistance against social changes that erode traditional values, using Richard Hoggart's critical cultural approach. This research was conducted using a qualitative-descriptive method through field observations, in-depth interviews, and literature reviews. The findings reveal that Tong-Tong Sèrèk serves not only as entertainment but also represents the spirit of collectivity, hard work, and the local identity of the Madurese community, which has been marginalised by dominant culture and the tide of modernisation. From Hoggart's perspective, this performance can be interpreted as a form of cultural expression by the people that preserves authentic values amid the expansion of mass culture. This study underscores the importance of preserving local traditions as a form of symbolic resistance and strengthening the cultural identity of communities increasingly threatened by the homogenisation of modern culture.